2017
DOI: 10.1177/1093526616686437
|View full text |Cite
|
Sign up to set email alerts
|

Melanotic Neuroectodermal Tumor of Infancy Presenting With Fast-Growing Scrotal Swelling

Abstract: Testicular melanotic neuroectodermal tumor of infancy (MNTI) is extremely rare, with 2 cases reported in the literature. Its rarity and rapid and infiltrative growth pattern pose a diagnostic challenge. A previously healthy 3-month-old male, presented with a history of worsening left hemiscrotal swelling for 1 week. An outside ultrasound was suggestive of testicular torsion. Left orchiectomy demonstrated a mass occupying almost entire testicle with a variegated cut surface, with areas of pigmentation, necrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This could be triggered by the host human-immune and parasite interaction, leading to the clearance of acute infection, which could have led to chronic clinical disease (hydrocele and lymphoedema) observed. In Figure 5A, the scrotal enlargements in the younger age group (5-11 years) were not hydrocele, but rather a condition possibly triggered by other conditions, such as congenital inguinal hernias, which are frequently seen in this age group [47], tumors, or tuberculosis. In this age group, hydroceles were not as common as in individuals aged 16-24 years [24,29].…”
Section: Discussionmentioning
confidence: 93%
“…This could be triggered by the host human-immune and parasite interaction, leading to the clearance of acute infection, which could have led to chronic clinical disease (hydrocele and lymphoedema) observed. In Figure 5A, the scrotal enlargements in the younger age group (5-11 years) were not hydrocele, but rather a condition possibly triggered by other conditions, such as congenital inguinal hernias, which are frequently seen in this age group [47], tumors, or tuberculosis. In this age group, hydroceles were not as common as in individuals aged 16-24 years [24,29].…”
Section: Discussionmentioning
confidence: 93%
“…2,3 It predominantly involves craniofacial sites in more than 90% of cases, and most commonly arises in the maxilla. 3,4 Rare, non-head and neck sites include epididymis, [5][6][7] testis, 8,9 ovaries, 10 and soft tissue and bones of the extremities. [11][12][13][14] The largest retrospective study 2 that reviewed 472 reported cases within the literature showed mainly maxillary involvement in 279 cases (62.2%), followed by the skull (70; 15%), mandible (35; 7%), male reproductive system (23; 5%), central nervous system (20; 4%), soft tissue (7; 1%), and female reproductive system (3; ,1%).…”
mentioning
confidence: 99%
“…Testicular, rete testis, and spermatic cord involvement have been reported. 6,7 CT typically reveals a hyperdense mass, but hypodense growths also have been reported. On a magnetic resonance imaging, the tumor appears isointense or hypointense on T1- and T2-weighted sequence and shows a contrast enhancement after gadolinium injection.…”
Section: Discussionmentioning
confidence: 99%